The development of student discipline management system for SMK Seri Jementah / Noraziah Mohd Darus - Mohd Darus, Noraziah (2015)
Student Discipline Management System (SDMS) is a web-based system that be develop to manage student discipline record for Sekolah Menengah Kebangsaan Seri Jementah (SMKSJ). Currently, this school still using paper based system to manage and record all the discipline information for each student. Related to that, a lot of problem occurred especially for the discipline teacher. Discipline teacher having a difficulty in calculating all the merit and demerit points for each student. During calculating the points for each student, discipline teacher realize that sometimes careless mistakes occurred from his side when calculating the points such as calculate twice or wrongly inserted the points because each merit demerit have their own points. Sometimes, discipline teacher also having a problem in searching the name of the merit demerit. Besides that, it might be a difficulty to discipline teacher to produce a statistic for the school and discipline graph for each student. In developing this project, graphing technique is being used in producing a discipline performance graph for each student. In developing this project, developer used System Development Life Cycle (SDLC) as a methodology for developing this system. In this methodology, developer covered Requirement Gathering, Requirement Analysis, Design and Develop Phase. All the findings are be included in this report and also be specify in document which are Software Requirement Specification (SRS) and Software Design Description (SDD). For the future, developer suggest other developers to improve this project by included testing phase as to make sure it fulfil the stakeholder requirement.